2005
DOI: 10.4314/bcse.v19i2.21134
|View full text |Cite
|
Sign up to set email alerts
|

<b>REMOVAL OF LEAD IONS FROM INDUSTRIAL WASTE WATER BY USING BIOMATERIALS – A NOVEL METHOD</b>

Abstract: ABSTRACT.A simple cost effective and eco-friendly method for the remediation of lead from industrial wastewater has been investigated. A novel biomaterial, Tridax procumbens (Asteraceae) a medicinal plant, was used for the removal of lead ions from synthetic wastewater and the method was also applied for real sample analysis. The operational pH of the experimental solution was fixed as 4.5. The optimum amount of bioadsorbent was 3.5 g. The Pb(II) ions removal efficiency of the raw bioadsorbent was also determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Similarly, the functional groups ▬OH, C═O, C▬N, iodate, and ▬NH 2 were responsible for Pb 2+ adsorption onto IDCC. FTIR analysis of ACLF revealed that the absorption peaks are related to various functional groups namely ▬OH group, aromatic C▬H stretch, aromatic C═C stretch, and phenolic C▬O stretch [27][28][29]. The responsible and accurate sorption sites for Pb 2+ adsorption onto synthesized adsorbents were ascertained by changes in FTIR band frequencies of assorted functional groups like ▬OH and ▬C═O, NH2, and ▬ NH(C═O)CH3.…”
Section: Case Studies For Pb 2+ Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the functional groups ▬OH, C═O, C▬N, iodate, and ▬NH 2 were responsible for Pb 2+ adsorption onto IDCC. FTIR analysis of ACLF revealed that the absorption peaks are related to various functional groups namely ▬OH group, aromatic C▬H stretch, aromatic C═C stretch, and phenolic C▬O stretch [27][28][29]. The responsible and accurate sorption sites for Pb 2+ adsorption onto synthesized adsorbents were ascertained by changes in FTIR band frequencies of assorted functional groups like ▬OH and ▬C═O, NH2, and ▬ NH(C═O)CH3.…”
Section: Case Studies For Pb 2+ Removalmentioning
confidence: 99%
“…Inadequacies in use of this process are that ion exchange resins must be regenerated once exhausted, which in turn the regeneration eventually causes serious secondary pollution. Ion exchange process is not economical and cannot be used on large scale [5,7,8,10,18,[23][24][25][26][27][28][29][30][31].…”
Section: Assorted Treatment Processes For Lead Removalmentioning
confidence: 99%
“…The possible gender of lead ions to the ecosystem through the soil, water, and air perform to necessity removing of Pb(П) .Lead ions (Inorganic form) causes a disturbance in central of the nervous system by chang the characteristics of the early organism [3].The pathway for entry of metals in to the environment was particularly industrial waste water in electroplating, metal industrial finishing, tannery process, chemical manufacturing and battery manufacturing industries [4]. In drinking water there must be the maximum permissible limit(MPL) of lead is about 0.05 ppm [5].Many methods like chemical precipitations, adsorption and convention [6][7][8][9][10][11], ion exchange [12],methods of membrane separation [13] and electro-remediation ways [14] available for waste water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A large portion of synthetic dye that is lost during the dyeing process could remain mainly intact, because they are stable to light, heat, oxidizing agents and aerobic biological degradation. The application of conventional physicochemical wastewater treatments (precipitation, sedimentation, ultrafltration, flotation, UV irradiation, ozonation and coagulation) is limited due to the poor dye removal or high operational costs, intensive energy requirement and limited adaptability to a wide range of effluents (Akar et al, 2009;Aksu and Isoglu, 2006;Barka et al, 2013;Singanan, 2003).…”
Section: Introductionmentioning
confidence: 99%